Rhinal and hippocampal event-related potentials as epileptogenic zone markers in the pre-surgical evaluation of temporal epilepsies: a systematic review - Morange, Daniela de Andrade; Amaral, Magali Teresópolis Reis; Martinez-Silveira, Martha Silvia; Trébuchon, Agnès (Arquivos de Neuro-Psiquiatria, 2023)
Background Cognitive event-related potentials (ERPs) allow for lateralization of the epileptogenic zone (EZ) to estimate the reserve of memory in the contralateral non-epileptogenic hemisphere, and to investigate the prognosis of temporal lobe seizure control in unilateral temporal lobe epilepsy (TLE).Objective To define the accuracy of cognitive evoked anterior mesial temporal lobe (AMTL-N400) and P600 potentials in detecting the epileptogenic zone in temporal lobe epilepsy (TLE), and second, to evaluate the possibility of using them as markers of cognitive outcome.Methods The systematic review using Medline/PubMed, Embase, and Lilacs database was conducted in September 2021. Only articles published in English from 1985 to June 2021 were included. We searched for studies with: (1) depth intracranial electroencephalography (iEEG) recordings analysis of rhinal and hippocampal activity (2) correlations between ERP results obtained in the mesial temporal regions (AMTL-N400 and P600) and the epileptogenic zone.Results Six out of the seven studies included in this review defined the laterality of the epileptogenic zone (EZ) during presurgical investigation using ERPs. One study showed that the contralateral AMTL-N400 predicts seizure control. Another study found correlation between the amplitudes of the right AMTL-N400 and postoperative memory performance.Conclusions There is evidence that the reduced amplitude of the AMTL-N400 has high accuracy in identifying the epileptogenic zone, as it does in estimating the extent of seizure control and memory impairment in postoperative patients.
Keywords: Evoked Potentials; Epilepsy; Temporal Lobe; Memory; Perirhinal Cortex; Hippocampus